DISKRIMINASI DAN RASIALISME DALAM FILM “AUSTRALIA” (STUDI ANALISIS SEMIOTIK FILM AUSTRALIA) - I Gusti Nugraha Jaya Perdana; Susilastuti DN; Christina Rochayanti (Jurnal Ilmu Komunikasi, 2009)
This research reveals all the signs and symbols of discrimination and racism in film Aus- tralia. The film is a film with a kind of fiction, but the story of the film is part of the true story of the conflict between the Aborigines by white men filled with the treatment of discrimination and racism. This behavior occurred since the arrival of white people who are British prisoners exiled to Australia. The white men then build a new colony by opening the land to the Aborigines being displaced into the interior, and they assume that the Aborigines are a group of people with an ancient culture and have no intellectual capacity so that their existence as a tribe native to Australia is considered bad by the people white. This research explores the signs of discrimination and racism in Australian films using triangulation from Roland Barthes’ semiotic theory is then obtained result is a representation of the meaning of discrimination and racism found in Australian films. In the study of signs and symbols in the film Australia. This research is also supported by the articles about the social reality in Australia, articles and discrimination and racism in the film text analysis. The research results obtained representation of the symbols of discrimination and racism contained in the Australian films that are part of everyday life between Aboriginal and white people. Discrimination and racism itself is still not an integral part of social life in Australia, and unfair behavior arbitrarily still frequently in Aboriginal gain by the existence of which began in get rid of white people.